Mass media guidelines for sports concussion: a scoping review protocol - Catherine Haden; Karen A Sullivan; Keeley Lappin; Kannan Singaravelu Jaganathan (BMJ Open Sport & Exercise Medicine, 2024)
Sports concussion is a common and costly injury, and increased public injury awareness could help reduce costs. Many factors, including public messages about sports concussion by the sports media, shape public injury awareness. Empirical analyses show that this messaging can be poor. The proposed solutions include providing media guidance, but little is known about this topic. This scoping review will enable a systematic search and synthesis of guidance materials for improved health messaging of sports concussion by the mass media. The five review stages are (1) determining the research question, (2) identifying relevant materials, (3) selecting relevant information, (4) data extraction and (5) analysis and presentation of the results. A brief protocol will be registered on a recommended platform (Open Science Framework). The search strategy will access 20 databases, as well as Google and Google Scholar, and include hand searching. Selected materials must describe or provide mass media guidance for sports concussion by a health-affiliated authority. Eligibility will be confirmed via a two-stage screening process, including independent assessment. Data from eligible materials will be extracted and collated in tables. If sufficient or appropriate materials are identified, the synthesis will draw on key evaluative resources related to injury management and guideline development methodologies. The knowledge synthesis will use descriptive and narrative methods to determine what is known on this topic, including documenting existing guidance (content and properties) and using the extracted data to inform recommendations for future guidance.